3D nanoporous Ag microstructures fabricated from AgCl microcrystal templates via concerted oxidative etching/re-deposition and galvanic replacement. Issue 35 (1st August 2016) - Gatemala, Harnchana; Thammacharoen, Chuchaat; Ekgasit, Sanong; Pienpinijtham, Prompong
Abstract : 3D nanoporous Ag microstructures (np-AgMSs) were successfully fabricated from AgCl microcrystal templates by a galvanic replacement approach using sacrificial Zn metal. Abstract : 3D nanoporous Ag microstructures (np-AgMSs) were successfully fabricated from AgCl microcrystal templates by a galvanic replacement approach using sacrificial Zn metal. This simple, rapid, and stabilizer-free protocol preserves the initial morphologies of AgCl microcrystal templates. The chloride ion is proven to be an essential ingredient in electrolytes as it facilitates the liberation of electrons from the sacrificial Zn metal. The formation mechanism of np-AgMSs via the reduction, at the AgCl/metal interfaces, of the mobile Ag + dissolved from AgCl is proposed. The concerted reaction between oxidative etching of np-AgMSs (by Cl − and Cl − /O2 ) and re-deposition of Ag atoms converts large grains to small grains. The grain size of np-AgMSs can be tuned by adjusting the concentration of Cl − . The np-AgMSs also show efficient catalytic activity for the reduction of p -nitrophenol by NaBH4 within 6 minutes for at least 10 cycles.